O-GlcNAc modification regulates autophagy and apoptosis in endometriosis - Xiaohan Jin; Yali Feng; Lei Xu; Jing Li; Linping Fan; Jinge Li; Runyuan Liu; Qing Yang; Ying Kong; Yuhong Shang (Functional & Integrative Genomics, 2026)

Electrochemical degradation of dibutyl phthalate in simulated printing and dyeing textile wastewater using cerium and stearic acid-modified Ti/TiO2-NTs/PbO2-Ce-SA electrode - Dexiang Liao; Fan Yang; Linping Tang; Fan Wu; Fang Yin; Lisu Chen; Daolun Feng (Journal of Water Process Engineering, 2026)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

First report of Michelia maudiae leaf blight caused by Colletotrichum siamense in China - Shaohua Huang; Jia Cao; Yuxuan Huang; Qianying Luo; Jiayu Luo; Qian Li; Jiahui Huang; Ningwei Mao; Pengmin Fan; Jie Feng; Linping Zhang (Crop Protection, 2025)

First report of anthracnose caused by Colletotrichum siamense on Cinnamomum burmanni - Jia Cao; Shaohua Huang; Yuxuan Huang; Jiayu Luo; Qianying Luo; Qian Li; Pengming Fan; Jiahui Huang; Ningwei Mao; Linping Zhang (Crop Protection, 2025)

Optimization of Phaeodactylum tricornutum cultivation for enhancing mariculture wastewater treatment and high value product recovery using Box–Behnken design - Feng You; Yiwei Fan; Linping Tang; Xiangrong Liu; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Process Safety and Environmental Protection, 2025)

POD-like nanozyme constructed from perspective of charge transfer engineering for biosensing of magnetic separation treated Listeria monocytogenes - Weiqiang Li; Xiaoyun Xu; Yang Song; Linping Fan; Jin Huang; Luyu Yang; Yang Liu; Hengyi Xu (Food Chemistry, 2025)

Research on Time-Cooperative Guidance with Evasive Maneuver for Multiple Underwater Intelligent Vehicles - Zuoe Fan; Hao Ding; Linping Feng; Bochen Li; Lei Song (Journal of Marine Science and Engineering, 2024)
In order to achieve the precise attack of multiple underwater intelligent vehicles (UIVs) on the same target ship at a fixed impact time, and to improve the penetration capability of the UIVs themselves, this study investigated the guidance law for the time-cooperative guidance of UIVs with maneuvering evasion. The evasive maneuver of the UIV increases the line-of-sight angle between the UIV and the target, which decreases the guidance precision of the UIV. A segmented control strategy is proposed to solve the problem of decreasing guidance precision caused by evading maneuvers, which is also the main contribution of this paper. This control strategy is dividing the guidance trajectory into two segments. The first segment allows for intelligent underwater vehicles to make evasion maneuvers and penetrate the defense, while the second segment controls the terminal time and achieves precision strike. Different desired target-vehicle distances are designed for each segment, unifying the impact time control issue and evasion maneuver problem into the pursuit of desired target-vehicle distances. Finally, based on feedback linearization control theory, a time-cooperative guidance law with evasion maneuver capability is proposed. Simulation results validate the effectiveness of the proposed method in attacking-moving targets.

Rapid activation of peroxymonosulfate with iron(Ⅲ) complex for organic pollutants degradation via a non-radical pathway - Shouying Wu; Wei Wu; Jianing Fan; Linping Zhang; Yi Zhong; Hong Xu; Zhiping Mao (Water Research, 2023)

Identification of a novel frameshift mutation in the SCNN1B causing Liddle syndrome - Yi Qu; Yiting Lu; Di Zhang; Xinchang Liu; Peng Fan; Jiexin Chen; Hanbo Zhang; Kunqi Yang; Tao Tian; Yi Zhou; Qiongyu Zhang; Yu Zhang; et al. (Science Bulletin, 2023)

Factors associated with dysglycemia and its post-surgical resolution in patients with pheochromocytomas - Lin Zhao; Xu Meng; Qiongyu Zhang; Yi Zhou; Ting Zhang; Tao Tian; Hua Fan; Huadong Zhu; Yecheng Liu; Fang Luo; Linping Wang; Weixian Yang; et al. (Science China Life Sciences, 2023)

Investigation of VOC characteristics, source analysis, and chemical conversions in a typical petrochemical area through 1-year monitoring and emission inventory - Guimei Qin; Song Gao; Qingyan Fu; Shuang Fu; Haohao Jia; Qingrui Zeng; Linping Fan; Huarui Ren; Jinping Cheng (Environmental Science and Pollution Research, 2022)

Integrated microRNA–mRNA analysis of coronary artery disease - Fei Chen; Xin Zhao; Juan Peng; LinPing Bo; Bing Fan; Duan Ma (Molecular Biology Reports, 2014)